Reingenieria de procesos al centro de interpretación de la comunidad Alao para mejorar el servicio al cliente. - Orozco Yánez, Gabriel Isaac (2016)
This paper aims to design a manual process for the interpretive center of Alao community through the identification and integration of attractions, services, facilities and activities to improve customer service. The facilities of the Interpretation lead us through history, in their natural, human and conservation contexts to implement new actions and fundamental decisions that give opportunity to better progress thereof. The research was conducted with the relevant literature review, in order to deepen knowledge of frameworks according to the nature of this study and a general interpretation center. The second chapter contains the methodological framework in which the methods, inductive and deductive which use techniques such as observation, surveys and interviews and instruments used to collect information and interview guide detailed the same as were tabulated and interpreted. The results obtained through the surveys and interviews was that visitors were not satisfied with respect to knowledge of the issues raised in the center of interpretation by the staff working in the same, just as the organization it does not filled the expectations of visitors.